Pengaruh Edukasi melalui Demostrasi Pembidaian Fraktur Tulang Panjang terhadap Pengetahuan dan Sikap Remaja di SMA Pusri Palembang - Ardianty, Septi; Agustin, Oca; Kurniati, Indah (Universitas Baiturrahim, 2025)
Background: Long bone injuries can occur anywhere and at any time, even in the school environment. Therefore, treatment or first aid for long bone fractures can be performed in the school environment. This study focuses on the impact of education on knowledge regarding long bone fractures. Research Objective: This study aims to determine whether health education influences adolescents' knowledge about first aid for long bone fractures at Pusri High School, Palembang. Research Method: This study used a quantitative research design with a pre-experimental design. This study used a one-group pre-test and post-test approach to assess the effect of education on knowledge about fractures. The study population was all Pusri High School students in Palembang, and the study sample consisted of 86 students selected using purposive sampling. Results: The median knowledge score before education was 9, and after education it increased to 12. Statistical testing using the Wilcoxon Test showed a significant p-value of 0.000. Conclusion: This indicates a statistically significant increase in knowledge.